1992
DOI: 10.1007/bf01744458
|View full text |Cite
|
Sign up to set email alerts
|

Deep negative T waves associated with reversible left ventricular dysfunction in acute adrenal crisis

Abstract: We report two cases of reversible left ventricular dysfunction associated with deep negative T waves during acute adrenal crisis due to isolated deficiency of adrenocorticotrophic hormone. There were no symptoms suggestive of heart disease in either case and left ventricular wall motion abnormalities, present mainly around the left ventricular apex, returned to normal in 1-2 weeks. Deep negative T waves normalized 4 weeks after corticosteroid administration. Acute adrenal crisis should be considered when deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…This state is usually termed adrenal crisis. However, cardiomyopathy induced by adrenal crisis is very uncommon (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…This state is usually termed adrenal crisis. However, cardiomyopathy induced by adrenal crisis is very uncommon (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Sudden unexpected death (2) and Cardiovascular complications of hypopituitarism have been described previously but reports of lethal cardiac arrhythmia are very rare (3-5) as are electrocardiographic changes in hypopituitarism (6, 7) the electrocardiographic changes that are considered to be associated with hypopituitarism are giant T inversion, QT prolongation and ST changes. The exact cause of electrocardiographic changes in such cases is not defined but hypoglycemia, catecholamine surge secondary to hypoglycemia and hypomagnesemia, or decrease ACTH level (2) are considered as possible cause, such changes mimics ischemia and intracranial pathology but in our patient coronary disease was ruled out by coronary angiography, other possible causes of QT prolongation such as genetic or drug induced may be considered in our case but history was negative for use of such medications and as seen in (Figure 1) the ECG in 29.4.2008 QT interval was normal before possible aggravation of endocrine condition which may have been triggered by discontinuation of drugs or emotional stress before onset of ventricular arrhythmia .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, because of the giant size of the T waves, the authors stated that "the patient was mobilized slowly because his electrocardiogram showed very deep (15 mm) symmetrical TWI in the chest lead". Iga et al [20] in 1992 reported on deep negative T waves associated with reversible left ventricular dysfunction in acute adrenal crisis. The left ventricular dysfunction normalized within 1-2 weeks and the deep negative T waves normalized after 4 weeks.…”
Section: Othersmentioning
confidence: 98%